Effect of Intravenous Immunoglobulin in Reducing Bilirubin Levels in Hemolytic Disease of Newborn - Saba Naim Khan , Tariq Saeed , Mehreen Batool Bukhari , Imran Mahmood Khan , Samiya Naeemullah; Mahwish Rabia (Journal of Rawalpindi Medical College, 2013)
Background: To assess the efficacy of intravenous immunoglobulins in reducing the duration of phototherapy and the need for exchange transfusion in neonates with Rh and/or ABO incompatibility. Methods: In this descriptive study 60 patients diagnosed with hemolytic disease of newborn were grouped into group A and B. All neonates were treated with standard protocol for phototherapy and exchange transfusion. Group A patients received intravenous immunoglobulins in a dose of 0.5gm/kg of body weight and phototherapy.Group B received only phototherapy. Exchange transfusion was given to the patients of both groups if the bilirubin reached 20mg/dl or more, or rose by 0.5 mg/dl per hour. Results:Mean pre and post treatment bilirubin levels were 14.87+ 4.45, 15.37+4.85 and 14.05+ 2.48, 14.35+1.97 mg/dl in group A and B respectively. Improvement in bilirubin level was significant in group A 82.75% vs 48.38 % (CI: 95%, P-value 0.005). Similarly phototherapy duration was reduced in the same group 86.2% vs 16.1% (p-0.000). Exchange transfusion and hospital stay were also reduced in group A 3.4% vs 48.4%, 35.49 % vs 86.20% (95% CI, P=0.000) respectively. Conclusion: Addition of intravenous immunoglobulins for treatment of hemolytic disease of newborn significantly reduces bilirubin levels, duration of phototherapy, need for exchange transfusion and hospital stay.